Blockage of the IL-31 Pathway as a Potential Target Therapy for Atopic Dermatitis - Raquel Leao Orfali; Valeria Aoki (MDPI AG, 2023)
Atopic dermatitis (AD), a pruritic, inflammatory chronic disease with multifactorial pathogenesis, has been a therapeutic challenge. Novel target treatments aim to reduce not only the immunologic dysfunction and microbiome dysbiosis but also the recovery of the damaged skin barrier. The current review focuses on the interleukin 31 (IL-31) pathway and AD and offers an overview of the current clinical studies with monoclonal antibodies blocking this cascade. Pruritus, the key symptom of AD, has substantial participation of the IL-31 complex and activation of relevant signaling pathways. Epidermal keratinocytes, inflammatory cells, and cutaneous peripheral nerves express the interleukin-31 receptor α-chain (IL-31RA), upregulated by Staphylococcus aureus toxins or Th2 cytokines involved in AD. Nemolizumab is a humanized monoclonal antibody that antagonizes IL-31RA, inhibiting the IL-31 cascade and therefore contributing to reducing the pruritus and inflammation and recovering the damaged skin barrier in AD patients. Phases 2 and 3 clinical trials with nemolizumab in AD show a suitable safety profile, with a fast, efficient, and sustained reduction of pruritus and severity scores, especially when associated with topical treatment. Deciphering the full interplay of the IL-31 pathway and AD may expand the potential of nemolizumab as a targeted therapy for AD and other pruritic conditions.